Germination Behaviour of Teak Genotypes and Effect of Different Treatments on Seed Germination Characteristics in Himalayan Foothills, India - Tewari, Salil; Tewari, Lakshmi; Kumar, Abhay; Bisht, Sarita; Kaushal, Rajesh; Kumar, Amit (Indian Forester, 2024)
Teak is becoming a more valuable plantation species due to its high dimensional stability and quality wood under changing weather conditions such as temperature and humidity. However, information regarding seed characteristics and seed handling of the species is meager. This study describes seed characteristics, germination behaviour and pre-treatment for enhancing seed germination of teak. The results of the present study revealed that stored seeds had a higher germination percentage than fresh seeds. The growth parameters were also observed to be higher in plants originating from stored seeds. Speed of germination, germination index, mean daily germination and peak value were also higher in stored seeds as compared to the fresh seeds. Treatment five had a higher germination percentage. The growth parameters of the seeds also higher in seedlings originated from stored seeds. The results of this study are helpful for the conservation and nursery practices of teak.